- Prediction of Serum Neuritin and Neuron-specific Enolase for Prognosis in Patients with Traumatic Brain Injury combined with Spinal Cord Injury: Neuritin and enolase prediction for brain + spinal cord injury patients - Pu, Bingbing (Journal of Medical Biochemistry, 2024)
Abstract: Serum neuritin and neuron-specific enolase (NSE) have predictive value for the prognosis of patients with combined traumatic brain injury (TBI) and spinal cord injury (SCI). Studying their predictive effects has positive value for disease control and treatment. Sixty patients with combined TBI and SCI were recruited and rolled into three groups according to prognosis: Group I (n=42, favorable prognosis), Group II (n=11, poor prognosis), and Group III (n=7, death). Clinical indicators were compared between the groups, and the predictive value of different indicators for prognosis was analyzed. NSE and serum neuritin levels were considerably higher in Groups II and III than in Group I (P
Keywords: Serum neuritin; Neuron-specific enolase; Traumatic brain injury; Spinal cord injury; Prognostic prediction.